Auranofin exerts broad-spectrum bactericidal activities by targeting thiol-redox homeostasis - Harbut, Michael B; Vilchèze, Catherine; Luo, Xiaozhou; Hensler, Mary E; Guo, Hui; Yang, Baiyuan; Chatterjee, Arnab K; Nizet, Victor; Jacobs, Jr, William R; Schultz, Peter G; Wang, Feng (Proceedings of the National Academy of Sciences - PNAS, 2015)
Infections caused by antibiotic-resistant bacteria are a rising public health threat and make the identification of new antibiotics a priority. From a cell-based screen for bactericidal compounds against Mycobacterium tuberculosis under nutrient-deprivation conditions we identified auranofin, an orally bioavailable FDA-approved antirheumatic drug, as having potent bactericidal activities against both replicating and nonreplicating M. tuberculosis. We also found that auranofin is active against other Gram-positive bacteria, including Bacillus subtilis and Enterococcus faecalis, and drug-sensitive and drug-resistant strains of Enterococcus faecium and Staphylococcus aureus. Our biochemical studies showed that auranofin inhibits the bacterial thioredoxin reductase, a protein essential in many Gram-positive bacteria for maintaining the thiol-redox balance and protecting against reactive oxidative species. Auranofin decreases the reducing capacity of target bacteria, thereby sensitizing them to oxidative stress. Finally, auranofin was efficacious in a murine model of methicillin-resistant S. aureus infection. These results suggest that the thioredoxin-mediated redox cascade of Gram-positive pathogens is a valid target for the development of antibacterial drugs, and that the existing clinical agent auranofin may be repurposed to aid in the treatment of several important antibiotic-resistant pathogens.